Synthesis, characterization and catalytic evaluation of H3PW12O40 included in acrylic acid/acrylamide polymer for the selective oxidation of sulfides - Frenzel, Romina Alejandra (2016)
A series of hybrid materials (SAPTPA) based on tungstophosphoric acid H3PW12O40 (TPA) included in acrylic acid/acrylamide polymer (SAP) were synthetized. The samples were characterized by FT-IR, XRD, 31P MAS-NMR, DTA-TGA, and the acidic properties were determined by means of potentiometric titration with n-butylamine. Materials with 10, 20, 30 and 40% (w/w) TPA content in the solid (SAPTPA10, SAPTPA20, SAPTPA30 and SAPTPA40, respectively) were prepared by impregnating the polymer with tungstophosphoric acid water solutions. According to FT-IR and 31P MAS-NMR studies, the main species present in the samples is the [PW12O40]3- anion, which was partially transformed into [P2W21O71]6- and [PW11O39]7- anions during the synthesis and drying steps. Taking into account XRD results, these species are highly dispersed in the polymer matrix or appear as noncrystalline phases. The DTA-TGA results show that SAPTPA materials did not undergo any remarkable chemical changes up to 200 °C. Additionally, the SAPTPA materials showed strong acid sites whose number increased as the TPA content in them was higher. The materials obtained by impregnation of TPA onto the polymer matrix present suitable physicochemical properties to be used as catalysts in the selective oxidation of sulfides to the corresponding sulfoxide/sulfone using acetonitrile as solvent and H2O2 35% w/v as a clean oxidant. The SAPTPA40 catalyst was appropriate for the selective sulfide oxidation in heterogeneous conditions and can be reused without significant loss of its catalytic activity. A convenient and selective procedure for oxidizing sulfides to sulfoxides or sulfones by varying the H2O2/substrate ratio and the temperature was found.